A method for preparing ultra-high temperature carbide ceramic coating by liquid phase method

Ultra-high temperature carbide ceramic coatings are prepared by a liquid phase method, and metal alloys are used to assist the solution to grow dense and uniform ceramic coatings on the substrate surface. This solves the problems of density and poor interface bonding strength of ultra-high temperature ceramic coatings in the existing technology, and achieves efficient and low-cost coating preparation.

CN120463500BActive Publication Date: 2025-10-10CENT SOUTH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510948442.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-07-10
Publication Date
2025-10-10
Estimated Expiration
2045-07-10

AI Technical Summary

Technical Problem

Existing methods for preparing ultra-high temperature ceramic coatings have problems such as high sintering temperature, high porosity, poor interface bonding, complex equipment and high cost, making it difficult to work stably in extremely high temperature environments.

Method used

The liquid phase method uses a metal alloy auxiliary solution to form a liquid alloy solution at high temperature, dissolve the carbon source and metal source, and grow a dense and uniform ultra-high temperature carbide ceramic coating on the surface of the substrate by controlling the temperature and time. The coating has strong bonding force and can seal the pores of the substrate.

Benefits of technology

It achieves high density, uniformity and excellent interface bonding strength, reduces porosity, improves the mechanical properties and thermal shock resistance of the material, simplifies equipment and reduces costs, and is suitable for complex-shaped substrates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120463500B_ABST
    Figure CN120463500B_ABST
Patent Text Reader

Abstract

The application discloses a method for preparing an ultra-high-temperature carbide ceramic coating by a liquid phase method. The method comprises the following steps: placing a base material in a graphite crucible, adding mixed powder to completely cover the base material, heating to melt the mixed powder to form an ultra-high-temperature alloy solution, carrying out a liquid phase reaction in a heat preservation mode, and finally lifting the base material away from the melt to obtain the ultra-high-temperature carbide ceramic coating. The mixed powder comprises an ultra-high-temperature metal powder and Si powder, and the molar ratio of the ultra-high-temperature metal powder to the Si powder is 0.15-0.65:0.2-0.6. The ultra-high-temperature metal powder is selected from at least one of Ta, Hf and Zr. The preparation method is controllable for the thickness of the coating, can obtain an ultra-high-temperature carbide ceramic coating with a relatively large thickness and a strong bonding force on the surface of the base material, and can seal the holes when depositing the coating on the surface of a base material containing holes, so that the compactness of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of ultra-high-temperature ceramic coating, in particular to a method for preparing an ultra-high-temperature carbide ceramic coating by a liquid phase method. BACKGROUND

[0002] Ultra-high-temperature ceramics (UHTCs) have an irreplaceable position in the modern high-tech field due to their excellent high-temperature resistance, high hardness, good chemical stability, and excellent thermal shock resistance. With the rapid development of aerospace, national defense, military industry, energy, and other industries, the demand for materials that can work stably in extreme high-temperature environments is increasingly urgent. For example, in the hot end parts of an aero-engine, such as the combustion chamber, turbine blade, and other parts, and in the key structures of a hypersonic aircraft, such as the leading edge and nose cone, materials are required to withstand high temperatures of up to 2000℃ or above. Ultra-high-temperature ceramics are one of the ideal materials to meet such demands.

[0003] Currently, there are many methods for preparing ultra-high-temperature ceramic coatings, such as powder metallurgy, chemical vapor deposition (CVD), physical vapor deposition (PVD), sol-gel method, and thermal spraying technology. Powder metallurgy prepares materials of the desired shape by molding and sintering ultra-high-temperature ceramic powders, but this method has high sintering temperature and is prone to produce defects such as pores, affecting the density and mechanical properties of the material. CVD can deposit high-quality ultra-high-temperature ceramic coatings on the surface of the substrate, but the equipment is complex, the cost is high, and the deposition rate is relatively low. PVD can deposit at a lower temperature, but the uniformity and adhesion of the coating still need to be improved. The sol-gel method dissolves the precursor material in a solvent to form a sol, and then prepares ceramic materials through drying and sintering steps. The ceramic materials prepared by the sol-gel method may have certain limitations in performance, such as density and hardness. Thermal spraying technology also cannot obtain a coating with good density, which is not conducive to improving oxidation resistance. In the process, the cooling rate is too fast, which can easily lead to excessive internal stress in the coating and cracking.

[0004] In the coating preparation process, the interfacial adhesion of the coating and the substrate, the adaptability of the complex-shaped substrate, the density and composition control of the coating need to be considered. Developing a method for preparing high-quality TaC, HfC, ZrC, and other ultra-high-temperature ceramic coatings has important practical significance and urgent market demand. SUMMARY

[0005] In response to the shortcomings of the prior art, the present invention aims to provide a method for preparing ultra-high temperature carbide ceramic coatings using a liquid phase process. The present invention utilizes a metal alloy as a solvent aid to form a liquid alloy solution at high temperature, dissolve a carbon source and a metal source, and, by controlling the temperature and time, causes the ultra-high temperature carbide ceramic to grow on the surface of the substrate, forming a dense, uniform, high-performance ceramic coating. The preparation method of the present invention allows for controllable coating thickness, resulting in a thicker, more strongly bonded ultra-high temperature carbide ceramic coating on the substrate surface. When the coating is deposited on a porous substrate surface, the pores can be sealed, thereby improving the density of the material.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] The present invention provides a method for preparing an ultrahigh temperature carbide ceramic coating by a liquid phase method, comprising placing a substrate in a graphite crucible, adding a mixed powder to completely cover the substrate, heating the mixed powder to melt the mixed powder to form an ultrahigh temperature alloy solution, maintaining the temperature for liquid phase reaction, and finally pulling the substrate out of the ultrahigh temperature alloy solution to obtain the ultrahigh temperature carbide ceramic coating.

[0008] The mixed powder comprises ultrahigh temperature metal powder and Si powder, and the molar ratio of ultrahigh temperature metal powder to Si powder is 0.15-0.65:0.2-0.6;

[0009] The ultra-high temperature metal powder is selected from at least one of Ta, Hf, and Zr.

[0010] The method of the present invention adopts a liquid phase method. In order to achieve the growth of ultra-high temperature carbide ceramics, it is necessary to ensure sufficient C solubility in the flux solution, because sufficient C solubility can provide enough C for the growth of ultra-high temperature carbide ceramic coatings. However, this does not mean that all flux solutions with sufficient C solubility are suitable for the growth of ultra-high temperature carbide ceramics. The condition for growing ultra-high temperature carbide ceramics by the liquid phase method is to ensure that the ultra-high temperature ceramic carbide phase is the only stable phase in the flux solution. If the ultra-high temperature ceramic carbide phase cannot exist stably in the solution, the ultra-high temperature ceramic carbide phase will be dissolved by the flux solution, and non-ultra-high temperature ceramic carbide phases may be generated on the surface of the substrate, and the ultra-high temperature ceramic carbide coating cannot be grown smoothly. When the ultra-high temperature ceramic carbide phase in the flux solution is the only stable phase in the flux solution, the ultra-high temperature ceramic carbide will reach the growth conditions, and when the ultra-high temperature ceramic carbide in the flux solution is the only phase that maintains a stable saturation state, the ultra-high temperature ceramic carbide coating will continue to grow, thereby achieving control of the coating thickness.

[0011] The present invention controls the molar ratio of ultrahigh temperature metal powder to Si powder so that ultrahigh temperature carbide is the only saturated phase in the ultrahigh temperature alloy flux, thereby obtaining an ultrahigh temperature ceramic carbide coating.

[0012] Therefore, it is necessary to effectively control the amount of ultra-high temperature metal added. If too much is added, the reaction temperature will increase, the temperature will increase, and the energy consumption will increase. If too little ultra-high temperature metal is added, it will be difficult to ensure that the ultra-high temperature ceramic phase in the auxiliary solution is the only stable saturated phase, and the growth conditions of ultra-high temperature ceramic carbides cannot be achieved.

[0013] In addition, in the present invention, the carbon source comes from the graphite crucible, which can be dissolved by the solvent to provide a carbon source, and through in situ nucleation, an ultra-high temperature ceramic carbide phase is formed. If the carbon source is added in the form of powder, carbon will be included in the coating, reducing the coating performance.

[0014] The method of the present invention can not only prepare a single coating, but also obtain a multilayer coating by repeatedly performing liquid phase reactions, and the coating has excellent bonding performance.

[0015] In a preferred embodiment, the substrate is fixed on a graphite rod and then placed in a graphite crucible.

[0016] In a preferred embodiment, the mixed powder completely covers the substrate to a height of 5 to 20 mm above the substrate. By increasing the coverage height to 5 to 20 mm above the substrate, the molten ultrahigh temperature alloy flux can completely immerse the substrate.

[0017] In a preferred embodiment, the mixed powder further comprises other metal powders, and the other metal powders are selected from at least one of Al, Ti, Cr, Ni, Y, Nd, Ce, and Sn, preferably Ni.

[0018] Further preferably, in the mixed powder, the molar ratio of ultrahigh temperature metal powder to other metal powder is 0.15-0.65:0.1-0.4.

[0019] The inventors have discovered that by further adding other metal powders, the temperature at which the raw materials melt into a liquid state can be lowered, thereby lowering the reaction temperature.

[0020] In a preferred embodiment, the mixed powder is composed of ultrahigh temperature metal powder, Si powder and other metal powders, and the molar ratio of ultrahigh temperature metal powder: Si powder: other metal powder is 0.5-0.6: 0.2-0.3: 0.2-0.3.

[0021] In a preferred embodiment, the substrate is selected from one of graphite, carbon-carbon composite material and carbon fiber.

[0022] In a preferred embodiment, the heating temperature is 1500-2100° C., and the holding time is 0.5-10 h.

[0023] Further preferably, the mixed powder is heated at a heating rate of 5-20°C / min under a protective atmosphere until it melts into a liquid state, forming an ultrahigh-temperature alloy flux solution. The temperature is then further increased to 50-300°C at a heating rate of 1-5°C / min and maintained at this temperature for 0.5-10 hours to carry out the liquid-phase reaction. Heating to initial melting of the powder can significantly shorten the process time, while slowly increasing the temperature to ensure thorough mixing of the flux solution, thereby obtaining a uniform flux solution. This facilitates the transport of substances in the flux solution and facilitates obtaining a highly uniform ultrahigh-temperature ceramic carbide coating.

[0024] Advantages and positive effects of the invention

[0025] 1. High density and uniformity

[0026] By using an ultra-high-temperature metal alloy flux to dissolve the carbon and metal sources in a liquid environment, the fluidity of the liquid allows the coating material to fully fill the microscopic pores on the substrate surface, forming a dense and uniform ceramic coating. Compared to traditional powder metallurgy or thermal spraying techniques, this method significantly reduces porosity and improves the material's mechanical properties and thermal shock resistance.

[0027] 2. Excellent interface bonding strength

[0028] The liquid-phase reaction environment promotes chemical bonding between the coating and the substrate, significantly improving the coating's adhesion. This is especially true on complex-shaped substrates, such as aircraft engine turbine blades, where the coating adheres tightly to the substrate, avoiding the interfacial delamination issues that can occur with traditional physical deposition (PVD / CVD).

[0029] 3. Process flexibility and controllability

[0030] By adjusting the temperature (1500-2100°C), holding time (0.5-10 hours), and the metal alloy ratio (such as the combination of Ta, Hf, Zr with Si, Al, Ti, Ci, Y, Nd, Ce, Sn, etc.), the thickness, composition, and microstructure of the coating can be controlled. For example, on the surface of porous substrates (such as carbon / carbon composites), the pores can be sealed by extending the holding time, significantly improving the material's oxidation resistance and density.

[0031] 4. Cost-effectiveness and equipment simplification

[0032] Compared to technologies like CVD / PVD, which rely on complex vacuum equipment, this liquid-phase method can be performed in conventional induction or resistance furnaces, significantly reducing equipment investment and process complexity. Furthermore, the high efficiency of the liquid-phase reaction shortens production cycles, making it suitable for large-scale industrial applications.

[0033] 5. Material diversity and adaptability

[0034] Supports the preparation of various ultra-high-temperature carbide coatings (TaC, HfC, ZrC) to meet the needs of various extreme environments (such as hypersonic vehicle nose cones and nuclear reactor inner walls). Its strong substrate compatibility, including graphite and carbon / carbon composites, expands its application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 , microstructure diagram of the tantalum carbide coating on the graphite surface prepared in Example 1.

[0036] Figure 2 , XRD spectrum of the tantalum carbide coating on the graphite surface prepared in Example 1.

[0037] Figure 3 , SEM image of the zirconium carbide coating on the graphite surface prepared in Example 2.

[0038] Figure 4 , XRD spectrum of the zirconium carbide coating on the graphite surface prepared in Example 2.

[0039] Figure 5 , SEM image of the cross section of the graphite substrate used in Comparative Example 1.

[0040] Figure 6 , SEM image of the graphite substrate surface used in Comparative Example 2, Figure 6 (a) is the SEM image of the original graphite surface. Figure 6 (b) is the SEM image of the graphite surface after the experiment. DETAILED DESCRIPTION

[0041] Example 1:

[0042] Tantalum (Ta) powder, silicon (Si) powder and nickel (Ni) powder are prepared in a molar ratio of 0.5:0.2:0.3 and mixed thoroughly. The prepared graphite substrate fixed on the graphite pull rod is placed in a graphite crucible, and the mixed raw materials are added thereto to completely cover the graphite substrate with a coverage height of 10 mm. The crucible is placed in an induction furnace. First, the pressure in the furnace is evacuated to below 200 Pa with a vacuum pump, and then 1.1 atm of Ar gas is introduced as a protective gas. Then, the temperature is raised to 1800°C at a rate of 10°C / min and kept warm for 30 minutes to allow the powder to initially melt. The temperature is then raised to 1900°C at a rate of 5°C / min and kept warm for 30 minutes. Subsequently, the substrate is pulled away from the liquid surface by a graphite pulling rod device and slowly cooled to room temperature. A tantalum carbide coating can be obtained on the graphite surface. The coating structure is shown in the attached figure. Figure 1 As shown in the figure, it can be seen that the coating and the graphite substrate are tightly bonded without gaps, the tantalum carbide grains are small, the grains are tightly bonded, and the density is high.

[0043] The XRD spectrum of the coating is as follows Figure 2As shown, it can be seen that the coating obtained by the present application is high-purity tantalum carbide.

[0044] Example 2

[0045] Zirconium (Zr) powder, silicon (Si) powder and nickel (Ni) powder were prepared in a molar ratio of 0.6:0.2:0.2, mixed thoroughly, and the prepared graphite substrate fixed on a graphite pulling rod was placed in a graphite crucible. The mixed raw materials were added to the graphite crucible to completely cover the graphite substrate with a covering height of 10 mm. The crucible was placed in an induction furnace. After the pressure in the furnace was vacuumed to below 200 Pa by a vacuum pump, 1.15 atm of Ar gas was introduced as a protective gas. The temperature was then raised to 1800 ℃ at a rate of 10 ℃ / min, and the powder was preliminarily melted for 30 min. The temperature was then continuously raised to 1950 ℃ at a rate of 3 ℃ / min, and the powder was kept at this temperature for 30 min. Then, the substrate was pulled away from the liquid surface by a graphite pulling rod device, and slowly cooled to room temperature. A ZrC coating on the surface of the graphite was obtained. Figure 3 As shown, the ZrC coating can be clearly seen in the figure, and the coating thickness is about 8.38 μm. The phase composition of the obtained coating is shown in Figure 4 As shown, the main phase is ZrC, with weak SiC and C peaks. The C peak is shown because the coating thickness is ultimately micron-level, so the substrate peak is shown, and only a weak SiC peak is shown, indicating that the purity of the ZrC coating is still very high, and only a small amount of SiC is generated by the reaction.

[0046] Comparative Example 1

[0047] The other conditions were the same as in Example 1, except that the molar ratio of tantalum (Ta) powder, silicon (Si) powder and nickel (Ni) powder was adjusted to 0.1:0.6:0.3. As a result, no obvious coating was generated on the surface of the graphite, as shown in Figure 5 As shown, no obvious coating was generated on the surface of the graphite.

[0048] Comparative Example 2

[0049] The other conditions were the same as in Example 2, except that the molar ratio of zirconium (Zr) powder, silicon (Si) powder and nickel (Ni) powder was adjusted to 0.1:0.8:0.1. As a result, as shown in Figure 6 As shown in (a) of Figure 6 (b) of Figure 6 As shown in (a) of (b) of the figure shows the SEM image of the surface of the graphite after the experiment. As can be seen from the figure, no coating was obtained on the surface of the graphite in the comparative example, and the surface of the graphite was slightly corroded.

Claims

1. A method for preparing an ultra-high temperature carbide ceramic coating by a liquid phase method, characterized in that: The substrate is placed in a graphite crucible, and the mixed powder is added to completely cover the substrate. The mixed powder is heated to melt the mixed powder to form an ultra-high temperature alloy solution. The temperature is kept to allow a liquid phase reaction to proceed. Finally, the substrate is pulled out of the ultra-high temperature alloy solution to obtain an ultra-high temperature carbide ceramic coating. The mixed powder is composed of ultra-high temperature metal powder, Si powder and other metal powders, and the molar ratio of ultra-high temperature metal powder: Si powder: other metal powder is 0.5-0.6:0.2-0.3:0.2-0.3; The ultra-high temperature metal powder is selected from at least one of Ta, Hf, and Zr.

2. The method for preparing an ultra-high temperature carbide ceramic coating by a liquid phase method according to claim 1, characterized in that: The substrate was fixed on a graphite rod and then placed in a graphite crucible.

3. The method for preparing an ultra-high temperature carbide ceramic coating by a liquid phase method according to claim 1, characterized in that: The mixed powder completely covers the substrate so that the coverage height exceeds the substrate by 5 to 20 mm.

4. The method for preparing an ultra-high temperature carbide ceramic coating by a liquid phase method according to claim 1, characterized in that: The other metal powder is selected from at least one of Al, Ti, Cr, Ni, Y, Nd, Ce, and Sn.

5. The method for preparing an ultra-high temperature carbide ceramic coating by a liquid phase method according to claim 4, characterized in that: The other metal powder is Ni.

6. The method for preparing an ultra-high temperature carbide ceramic coating by a liquid phase method according to claim 1, characterized in that: The substrate is selected from one of graphite, carbon-carbon composite material and carbon fiber.

7. The method for preparing an ultra-high temperature carbide ceramic coating by a liquid phase method according to claim 1, characterized in that: The heating temperature is 1500-2100° C., and the insulation time is 0.5-10 hours.

8. The method for preparing an ultra-high temperature carbide ceramic coating by a liquid phase method according to claim 1, characterized in that: Under a protective atmosphere, heat the mixture at a heating rate of 5-20°C / min until the mixed powder melts into a liquid state to form an ultra-high temperature alloy auxiliary solution, then heat it again at a heating rate of 1-5°C / min to 50-300°C and keep it warm for 0.5-10 hours to carry out liquid phase reaction.

Citation Information

Patent Citations

  • Preparation method of multi-component carbide ceramic coating

    CN116639980A

  • Method for producing silicon carbide single crystal

    JP2008169111A